The role of Qishen Yiqi dripping pills in treating chronic heart failure: An overview of systematic reviews and meta-analyses - Chen, Wensheng; Chen, Jiezhen; Wang, Yuanping; Yan, Jiaqi; Yan, Xia; Wang, Dawei; Liu, Yuntao (Frontiers in Cardiovascular Medicine, 2022)
Objectives Evidence from systematic reviews/meta-analyses about the efficacy and safety of Qishen Yiqi (QSYQ) dripping pills in chronic heart failure (CHF) remains unclear. This study comprehensively reviewed available systematic reviews on latest evidence to provide reliable information for the clinical use of QSYQ in CHF. Methods The systematic review was performed on studies retrieved from six major medical databases. Eligible studies were evaluated in terms of methodological quality and quality of evidence using the Assessment of Multiple Systematic review 2 (AMSTAR-2) tool, the Risk of Bias in Systematic Reviews (ROBIS) was used to assess the risk of bias, and the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) 2020 was utilized for assessing reporting quality. In addition, the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to determine primary outcome indicators’ evidence quality. Results A total of 14 systematic reviews were included in this study, based on which it could be concluded that QSYQ combined with conventional medicine (CM) treatment tended to be superior to CM treatment alone in terms of improving cardiac function-related indices (e.g., increasing the left ventricular ejection fraction [LVEF] and reducing the left ventricular end-diastolic dimension [LVEDD] and left ventricular end-systolic internal diameter [LVESD]), improving the total effective rate and 6-min walking distance (6MWD), and reducing N-terminal pro-brain natriuretic peptide (NT-proBNP). Overall, no serious QSYQ-related adverse events were observed. However, the GRADE results showed “very low” to “moderate” evidence for these outcomes, with no high-quality evidence supporting them. Unsatisfactory results were obtained in terms of methodological quality, risk of bias and reporting quality after assessment using the AMSTAR-2, ROBIS, and PRISMA 2020, limited mainly by deficiencies in the following areas: registration of study protocols, explanation of the inclusion of randomized controlled trials (RCTs), complete and detailed search strategy, list of excluded literature, description of funding sources for inclusion in RCTs, investigation of the impact of risk of bias on the results of meta-analysis, and reporting of potential conflicts of interest. Conclusion The efficacy and safety of QSYQ adjuvant therapy in CHF remain to be further clarified due to the lack of high-quality evidence provided by current systematic reviews.